American Head and Neck Society Endocrine Surgery Section and International Thyroid Oncology Group consensus statement on mutational testing in thyroid cancer: Defining advanced thyroid cancer and its targeted treatment. Issue 6 (11th March 2022) - Shonka, David C.; Ho, Alan; Chintakuntlawar, Ashish V.; Geiger, Jessica L.; Park, Jong C.; Seetharamu, Nagashree; Jasim, Sina; Abdelhamid Ahmed, Amr H.; Bible, Keith C.; Brose, Marcia S.; Cabanillas, Maria E.; Dabekaussen, Kirsten; et al.
Abstract: Background: The development of systemic treatment options leveraging the molecular landscape of advanced thyroid cancer is a burgeoning field. This is a multidisciplinary evidence‐based statement on the definition of advanced thyroid cancer and its targeted systemic treatment. Methods: An expert panel was assembled, a literature review was conducted, and best practice statements were developed. The modified Delphi method was applied to assess the degree of consensus for the statements developed by the author panel. Results: A review of the current understanding of thyroid oncogenesis at a molecular level is presented and characteristics of advanced thyroid cancer are defined. Twenty statements in topics including the multidisciplinary management, molecular evaluation, and targeted systemic treatment of advanced thyroid cancer are provided. Conclusions: With the growth in targeted treatment options for thyroid cancer, a consensus definition of advanced disease and statements regarding the utility of molecular testing and available targeted systemic therapy is warranted.